Traditional Cough Remedies in Children: A Pediatric Emergency Medicine Perspective - Bilge Akkaya; Nilden Tuygun (Academic Journal of Health, 2026)
We read with great interest the study by Yanık et al. entitled "Traditional Remedies for Cough: Herbal Tea and Honey Use Among Adults in A Primary Care Setting"1. The authors effectively demonstrated that the use of herbal tea and honey is highly prevalent among adults presenting with cough, revealing its close association with sociocultural factors. While this study is invaluable for understanding traditional treatment tendencies in the community, we believe it would be beneficial to evaluate these findings in the context of several critical points regarding the pediatric age group. Cough is one of the most common reasons for admission to pediatric emergency departments, and caregivers frequently resort to various traditional methods before seeking professional medical care. The impact of these practices is not limited to pharmacological outcomes alone. Such interventions can alter caregivers' perception of symptom severity and influence the timing of professional healthcare utilization, potentially leading to delays in diagnosing serious underlying diseases. Honey, which has been reported to provide symptomatic relief in adults, is also widely used in children. Studies show that honey can reduce cough severity and improve sleep quality in children over one year of age2. However, its administration requires specific caution. Due to the risk of infant botulism, honey is strictly contraindicated in infants under 12 months 3. Despite this, the public perception of honey as "natural and harmless" can lead caregivers to overlook this crucial safety warning. Similarly, the use of herbal products—which often lack standardized ingredients and dosages—poses potential risks in the pediatric population. Unexpected adverse effects may arise due to variations in plant species, preparation methods, and administered quantities. Although severe adverse events are rare, allergic reactions, gastrointestinal side effects, toxicity, and herb-drug interactions must be carefully considered in pediatric practice4. For instance, even for linden (Tilia spp.), which is widely utilized and perceived as safe by the public, the European Medicines Agency does not recommend its use in children under 4 years of age due to insufficient data supporting its safety and efficacy2. This underscores that even the most common herbal products may lack adequate evaluation regarding their safety and efficacy in children. The high prevalence rates demonstrated by Yanık et al. deliver a crucial message to clinicians. When evaluating children presenting to the emergency department with a cough, it is essential to systematically question not only the current symptoms but also the traditional or complementary methods administered by caregivers prior to admission5. This approach can facilitate both the recognition of potential adverse effects and the accurate interpretation of the natural course of symptoms. We congratulate the authors for their valuable study, and we hope that drawing attention to pediatric safety issues regarding the use of traditional cough remedies will contribute to raising awareness in this field.